Jawabanmu

2014-01-16T17:44:23+07:00
-3(y-2)+48=2(y+7
-6y+48=14y
-63y+14y
y=14/63
=0.2

2(x+3)+2(x-4)=10
6x+(-8x)=10
14x²=10
x²=10/14
=0.7
semoga benar :)
2014-01-16T17:45:50+07:00
1) -3(y-2)+48=2(y+7)
-3y+6+48=2y+14
-3y-2y=14-6-48
-5y = -40
y= -40/-5
y = 8

2) 2(x+3)+2(x+4)=10
2x+6+2x+8= 10
2x+2x = 10-6-8
4x = -4
x=-1
Thanks untuk jawabannya ;)
ya sama sama...
1. -3(y-2)+48=2(y+7)
-3y + 6 +48 = 2y +14
-3y + 54 = 2y +14
54- 14 = 2y + 3y
40 = 5y
y = 40 : 5
y =8

2. 2(X+3)+2(X-4)=10
2x + 6 +2x-8 =10
4x -2 = 10
4x = 10+2
4x = 12
x=12 : 4
x= 3
oh ya benar yg ini, soalnya saya salah lihat soal yg no 2